2019
DOI: 10.3892/ijmm.2019.4100
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA inhibits lipopolysaccharide‑induced inflammatory responses through the TLR4/TAK1/NF‑κB signaling pathway in vascular smooth muscle cells

Abstract: To aim of the present study was to determine whether Tanshinone IIA (Tan IIA) inhibits lipopolysaccharide (LPS)-induced inflammation in vascular smooth muscle cells (VSMcs) from rats and elucidate the underlying molecular mechanism. VSMcs were primarily cultured and then treated with LPS (1 µg/l) and Tan IIA (25, 50 and 100 µmol/l) for 24 h. Monocyte chemoattractant protein (McP)-1, interleukin (IL)-6 and tumor necrosis factor (TNF)-α levels were detected by ELISA and reverse transcription-quantitative polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…50 The TNF-α is an inflammatory cytokine and its expression level reflects the pathogenesis and severity of the inflammatory process. According to Meng et al, 51 in-vitro study, in VSMCs, LPS-induced inflammatory responses were found to be inhibited via tan-IIA by partially suppressed TLR4/TAK1/NF-κB signaling cascade. The results showed that by using tan-IIA, the neuronal TLR-4 and NF-κB expression levels were found to be reduced, while inflammatory cytokines production and neuronal oxidative stress levels were found to be elevated.…”
Section: Inflammation-related Signal Transduction Pathway Toll-like Receptor/nf-κb Pathwaymentioning
confidence: 98%
“…50 The TNF-α is an inflammatory cytokine and its expression level reflects the pathogenesis and severity of the inflammatory process. According to Meng et al, 51 in-vitro study, in VSMCs, LPS-induced inflammatory responses were found to be inhibited via tan-IIA by partially suppressed TLR4/TAK1/NF-κB signaling cascade. The results showed that by using tan-IIA, the neuronal TLR-4 and NF-κB expression levels were found to be reduced, while inflammatory cytokines production and neuronal oxidative stress levels were found to be elevated.…”
Section: Inflammation-related Signal Transduction Pathway Toll-like Receptor/nf-κb Pathwaymentioning
confidence: 98%
“…Tanshinone IIA (Tan IIA) is a lipophilic components deriving from the roots of Chinese herbs medicine Salvia miltiorrhiza Bunge 17. Tan IIA has been found to possess a number of biological activities, such as anti-inflammation, anti-oxidant and anti-tumor activities 1820. Liu et al found that Tan IIA significantly inhibited the tumor growth of A549 human NSCLC xenografts 21.…”
Section: Introductionmentioning
confidence: 99%
“…17 Tan IIA has been found to possess a number of biological activities, such as anti-inflammation, anti-oxidant and anti-tumor activities. [18][19][20] Liu et al found that Tan IIA significantly inhibited the tumor growth of A549 human NSCLC xenografts. 21 Meanwhile, Tan IIA could induce apoptosis in NSCLC cells via downregulation the level of p-Akt.…”
Section: Introductionmentioning
confidence: 99%
“…To date, TLR2 and TLR4 have been increasingly recognized to share common pathways, eliciting synergetic effects on inflammatory responses such as vascular inflammation [5]. Previous literature reported that IL-6 was modulated by TLR2-dependent NF-κB activation in VSMCs [16], and so was TLR4 [17]. Collectively, IL-6-driven vascular inflammation is tightly regulated by a complicated network of signaling pathways.…”
Section: Introductionmentioning
confidence: 99%